2013
DOI: 10.2337/db12-1256
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Epithelial-to-Mesenchymal Transitioning Enhances Ex Vivo Reprogramming of Human Exocrine Pancreatic Tissue Toward Functional Insulin-Producing β-Like Cells

Abstract: Because of the lack of tissue available for islet transplantation, new sources of β-cells have been sought for the treatment of type 1 diabetes. The aim of this study was to determine whether the human exocrine-enriched fraction from the islet isolation procedure could be reprogrammed to provide additional islet tissue for transplantation. The exocrine-enriched cells rapidly dedifferentiated in culture and grew as a mesenchymal monolayer. Genetic lineage tracing confirmed that these mesenchymal cells arose, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 49 publications
(53 reference statements)
6
63
0
Order By: Relevance
“…More recently, the above results were confirmed in vitro using first the AR42J acinar cell line (113,114), and subsequently primary human pancreatic exocrine cells cultured in conditions that prevented epithelial-tomesenchymal transition (114). While not as ready as hematopoietic stem cells for clinical prime time, reprogramming of human exocrine tissues offers a most promising alternative to the use of stem cells, especially considering that the exocrine compartment of the pancreas makes up to 95% of the pancreas and is now routinely discarded after every clinical islet preparation.…”
Section: Cell Reprogrammingsupporting
confidence: 63%
“…More recently, the above results were confirmed in vitro using first the AR42J acinar cell line (113,114), and subsequently primary human pancreatic exocrine cells cultured in conditions that prevented epithelial-tomesenchymal transition (114). While not as ready as hematopoietic stem cells for clinical prime time, reprogramming of human exocrine tissues offers a most promising alternative to the use of stem cells, especially considering that the exocrine compartment of the pancreas makes up to 95% of the pancreas and is now routinely discarded after every clinical islet preparation.…”
Section: Cell Reprogrammingsupporting
confidence: 63%
“…Reprogramming variability is also observed in exocrine cell populations. In fact, the incapacity for b-cell differentiation of contaminating stromal cells arising from unselected exocrine cultures was recently described using transcription factor-based protocols (Lima et al, 2013). Hence, we were able to derive insulin + cells from HDDCs but not from freshly plated DCs or from stromal cells.…”
Section: Discussionmentioning
confidence: 83%
“…A similar observation was also reported in the transformation of mesenchymal cells. Glucagonsecreting alpha-like cells were generated by transfecting monolayer mesenchymal cells derived from pancreatic tissue exocrine with adenoviruses containing Pdx1, Ngn3, MafA, and Pax4 genes (Lima, 2013). This study also suggested that the formation of epithelial-like clusters of exocrine-derived mesenchymal stromal cells promotes the generation of IPCs.…”
Section: Discussionmentioning
confidence: 99%